Management of opioid-induced constipation in palliative patients with disseminated cancer - Klaudia Zacher; Gabriela Prucnal; Karolina Ryba; Karolina Ochyra; Kornelia Pudło; Martyna Bukała; Katarzyna Znamirowska; Jowita Frydrych; Patrycja Walkiewicz; Anna Rakoczy (Quality in Sport)
Stool constipation is one of the most common afflictions affecting palliative patients with advanced cancer. The widespread use of opioids in the analgetic treatment of this group of patients exacerbates the already existing problem of constipation or is the underlying cause of its occurrence. Often, however, the etiology of the condition appears to be multifactorial. This article discusses the effects of opioids on the gastrointestinal tract as a cause of constipation, other possible causes of constipation in palliative patients, helpful definitions and how to diagnose constipation in this group of patients. Another important topic highlighted is the possibility of gastrointestinal obstruction and the possible management of its presence. Finally, the management of constipation is discussed, taking into account both non-pharmacological and pharmacological treatment with traditional laxatives and peripheral opioid receptor antagonists (naldemedine, naloxegol, methylnaltrexone). The article is based on an analysis of the available scientific literature and cited sources.